Transparent sapphire ceramic connecting method based on glass solder
By connecting transparent sapphire ceramics with specific ingredients, the problem of difficulty in preparing large-size ceramics is solved, and high-strength and high-transparency joints are achieved, meeting the needs of high-temperature applications.
Patent Information
- Application Number
- CN202411802764.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
AI Technical Summary
Due to the limitation of production equipment, large-size sapphire transparent ceramics are difficult to prepare and costly, and existing welding technology is difficult to achieve high-strength and high-transparency joints.
The glass solder of specific components is used for connection. The raw material composition of the glass solder includes RE2O3, Al2O3, SiO2, B2O3, BaO and K2O. The glass solder powder is prepared by melt-water quenching method, and high-strength and high-transmittance joints are formed through presintering, joint assembly, joint connection and annealing.
The high strength and high light transmittance of transparent sapphire ceramic joints are achieved, which inhibits the crystallization of the joints, ensures the light transmittance of the joints, and meets the needs of high-temperature applications.
Smart Images

Figure CN119638471A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of welding, and in particular to a method for connecting transparent sapphire ceramics based on glass solder. Background Art
[0002] Transparent sapphire ceramics offer excellent properties, including high mechanical strength, chemical stability, and high transmittance in the ultraviolet, visible, and infrared regions. They hold broad application prospects in solid-state lasers, missile domes, infrared windows, and transparent armor. However, due to limited production equipment, producing large-scale transparent sapphire ceramics is difficult and expensive. Welding small components into larger ones is an effective solution to this problem.
[0003] Glass solder offers excellent optical transparency and good chemical compatibility with ceramic materials. Its physical and chemical properties, such as thermal expansion coefficient and refractive index, can be manipulated through the design of its composition. Therefore, glass solder is an ideal material for joining ceramics. However, to ensure optical transparency of the joint, it is necessary to suppress crystallization. Therefore, a high-strength and high-transmittance joining method for sapphire ceramics must be developed. Summary of the Invention
[0004] The object of the present invention is to provide a method for connecting transparent sapphire ceramics based on glass solder, by using glass solder with specific composition for connection, a sapphire ceramic joint with both high strength and high transmittance is obtained.
[0005] To achieve the above purpose, the technical solutions adopted by the present invention are as follows:
[0006] A method for connecting transparent sapphire ceramics based on glass solder is disclosed. The method uses glass solder to connect transparent sapphire ceramics. The raw material composition of the glass solder is as follows, calculated by weight percentage:
[0007] RE2O3: 30% to 40%, Al2O3: 5% to 10%, SiO2: 30% to 40%, B2O3: 10% to 20%, BaO: 5% to 10%, K2O: 5% to 10%.
[0008] The RE2O3 in the solder component of the glass solder for infiltrating and connecting sapphire ceramics is one or more of white La2O3 and Y2O3.
[0009] In the glass solder composition, B2O3 is introduced from H3BO3, K2O is introduced from K2CO3, and BaO is introduced from BaCO3.
[0010] In the glass solder composition, the purity of each raw material is higher than 99.9%.
[0011] The method for connecting transparent sapphire ceramics based on glass solder specifically includes the following steps:
[0012] (1) Material preparation: After grinding and polishing the surface of the sapphire ceramic to be welded, ultrasonically clean it with acetone for 5-20 minutes and blow dry it for later use;
[0013] (2) Preparation of glass solder: Weigh the various oxide raw materials according to the composition of the glass solder, mix them evenly, and then use the melting-water quenching method to prepare the glass solder powder;
[0014] (3) Solder pre-sintering: Add polyvinyl alcohol to the glass solder powder and stir evenly, then put it into a tableting mold to press it into a sheet structure with a certain thickness, and then put it into a muffle furnace for pre-sintering to obtain a glass solder sheet;
[0015] (4) Joint assembly: Cut the pre-sintered glass solder sheet into a shape with the same size as the ceramic surface to be welded, and then place it between two polished sapphire ceramics to form a "sandwich" assembly structure. No pressure is applied during the connection process.
[0016] (5) Joint connection: Place the joint assembled in step (4) in an air atmosphere muffle furnace and quickly heat it to the welding temperature, and keep it warm for a long enough time. After the insulation is completed, quickly cool it to room temperature;
[0017] (6) Joint annealing: Place the welded joint into the muffle furnace again in an air atmosphere, heat it to a certain temperature, keep it warm for a certain period of time, and then cool it to room temperature with the furnace.
[0018] In the step (1), the grinding and polishing method is: grinding with 600#, 1000#, and 1200# sandpaper in sequence, and then polishing with diamond polishing liquid with particle sizes of 2.5μm, 1.5μm, and 0.5μm in sequence.
[0019] In the step (2), the process of preparing the glass solder powder by the melt-water quenching method is as follows: weighing the oxide raw material powder into a polytetrafluoroethylene ball mill, using alcohol as the ball milling medium and ZrO2 as the grinding balls for ball milling, the ball milling speed is 400-500 rpm, and the ball milling time is 2-5 hours; drying after the ball milling is completed, pouring the dried material into a platinum crucible, and placing it in a muffle furnace with an air atmosphere and heating it to 1500-1600°C. After keeping the temperature for 1-3 hours, pouring the obtained glass melt into deionized water to obtain glass fragments; placing the glass fragments into an agate ball mill, using agate as the grinding balls for ball milling, the ball milling speed is 400-500 rpm, and the ball milling time is 2-5 hours. After the ball milling is completed, drying is performed and the glass solder powder is obtained by passing through a 200-mesh sieve.
[0020] In the step (3), the weight of the added polyvinyl alcohol is 1-5% of the weight of the glass solder powder; the pressed thickness of the flake glass solder is 0.1-0.3 mm, the pressure during pressing is 20-40 MPa, and the holding time is 1-5 min.
[0021] In the step (5), the heating rate of the joint connection process is: 5-20°C / min, the connection temperature is: 1400-1550°C, the holding time is 10-30min, the cooling rate between the welding temperature and 750°C is higher than 40°C / min, and there is no requirement for the cooling rate below 750°C.
[0022] In step (5), the following cooling methods can be used: inert gas can be introduced into the furnace to accelerate the cooling of the joint to ensure that the cooling rate of the joint is higher than 40°C / min; the joint can also be taken out of the furnace and allowed to cool naturally in the air.
[0023] In the step (6), the joint annealing temperature is 800-860° C., and the annealing time is 2-5 hours.
[0024] The design mechanism and beneficial effects of the present invention are as follows:
[0025] 1. The glass solder of the present invention contains no light-absorbing ions, resulting in excellent light transmittance. RE2O3 and BaO in the glass solder increase the refractive index of the glass, bringing the refractive index of the glass solder close to that of sapphire ceramics. The high RE2O3 content in the glass solder ensures a high softening temperature, meeting the requirements of high-temperature applications. The addition of K2O further increases the thermal expansion coefficient, bringing it close to that of sapphire ceramics.
[0026] 2. All components in the solder will not color the glass solder, and the final glass solder is colorless and transparent.
[0027] 3. The glass solder obtained by the present invention has excellent wettability on the surface of transparent sapphire ceramics, and the thermal expansion coefficient of the glass solder is very close to that of transparent sapphire ceramics, and the joint strength is high.
[0028] 4. On the one hand, the glass solder obtained by the present invention has a refractive index close to that of sapphire. On the other hand, by setting a reasonable connection temperature, holding time, and cooling rate, the present invention suppresses the interface reaction between the base material and the solder and the glass crystallization in the weld, thereby achieving a completely glassy weld. These two factors together ensure excellent light transmittance of the joint. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a photo of the joint microstructure obtained in Example 1.
[0030] Figure 2 This is the XRD pattern of the joint weld obtained in Example 1. DETAILED DESCRIPTION
[0031] The present invention will be further described below with reference to the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it. However, the embodiments are not intended to limit the present invention.
[0032] Example 1
[0033] This embodiment is a method for connecting transparent sapphire ceramics using glass solder, comprising the following steps:
[0034] (1) Material preparation: Grind the surface of the sapphire ceramic to be welded using 600#, 1000#, and 1200# sandpaper in sequence. Then, polish the surface of the ceramic to be welded using diamond polishing fluid with particle sizes of 2.5μm, 1.5μm, and 0.5μm in sequence. The polished sapphire ceramic is ultrasonically cleaned with acetone for 20 minutes and then blown dry for later use. The joint dimensions for mechanical performance testing are: 3×4×36mm, and the joint dimensions for optical performance testing are: 10×10×3mm.
[0035] (2) Preparation of Glass Solder: The components and mass fractions of the glass solder used are: La2O3: 35%, Al2O3: 5%, SiO2: 35%, B2O3: 15%, BaO: 5%, and K2O: 5%. An electronic balance is used to weigh the oxide raw materials according to the above proportions, with B2O3 introduced from H3BO3, BaO from BaCO3, and K2O from K2CO3. The weighed oxide raw material powders are placed in a polytetrafluoroethylene ball mill and ball milled using alcohol as the milling medium and ZrO2 as the grinding balls at a speed of 400 rpm for 4 hours. After ball milling, the mixed powder is dried on a heating platform at 80°C for 5 hours. The dried material is poured into a platinum crucible, and placed in a muffle furnace with an air atmosphere and heated to 1550°C. After keeping warm for 1-3 hours, the obtained glass melt is poured into deionized water to obtain glass fragments; the glass fragments are placed in an agate ball mill and ball milled with agate as grinding balls at a ball milling speed of 400 rpm for 4 hours. After ball milling, the material is dried and passed through a 200-mesh sieve to obtain the glass solder powder.
[0036] Solder pre-sintering: Add 2% polyvinyl alcohol (PVA) by weight to the glass frit and stir thoroughly. The mixture is then placed in a tableting mold and held at 20 MPa for 5 minutes. The tablets are pressed into 0.2 mm thick sheets. The sheets are then heated in a muffle furnace at a rate of 10°C / min to 800°C, held at that temperature for 30 minutes to densify the solder. The sheets are then cooled to room temperature and ready for use.
[0037] (4) Joint assembly: Cut the pre-sintered glass solder sheet into a shape with the same size as the surface of the ceramic to be welded, and then place it between two polished ceramics to form a "sandwich" structure.
[0038] (5) Joint connection: Place the assembled joint into an air-filled muffle furnace and heat it. Do not apply any pressure during the connection process. Rapidly heat to 1450°C at a rate of 30°C / min and hold for 50 minutes. Do not apply any pressure during the connection process. After the holding period, remove the joint from the furnace and quickly cool it to room temperature.
[0039] (6) Joint annealing: Place the welded joint in an air atmosphere muffle furnace again, heat it to 800℃ and keep it for 2h, then cool it to room temperature in the furnace.
[0040] Figure 1 The following is a microstructure photograph of the joint obtained in Example 1. It can be seen from the figure that no reaction products are formed at the sapphire ceramic / glass solder interface. Furthermore, the weld is not crystallized, but in a completely glassy state with no crystal precipitation. Figure 2 The XRD pattern of the weld shows a typical "steamed bun" peak, further proving that the weld is completely glassy. This ensures the light transmission of the resulting joint, with a bending strength of 382 MPa and a light transmittance of 82.2% at 1064 nm.
[0041] Example 2
[0042] In step (2), 35% of La2O3 in the main component of the glass solder was replaced with 35% of Y2O3, and the other steps were the same as those in Example 1. The joint obtained in this example had a bending strength of 385 MPa and a light transmittance of 82.3% at a wavelength of 1064 nm.
[0043] Example 3
[0044] In step (2), the main components of the glass solder, 35% La2O3, were changed to 20% La2O3 and 15% Y2O3. The other steps were the same as those in Example 1. The joint obtained in this example had a bending strength of 374 MPa and a light transmittance of 82.5% at a wavelength of 1064 nm.
[0045] Example 4
[0046] In step (5), the cooling rate of the joint from 1450°C to 750°C was set at 50°C / min. Since the furnace's cooling rate was lower than 50°C / min when the power was off, argon gas was introduced into the furnace to increase the cooling rate. When the furnace temperature dropped below 750°C, the joint was allowed to cool with the furnace. The other steps were the same as in Example 1. The joint obtained in this example had a bending strength of 393 MPa, and a light transmittance of 82.3% at a wavelength of 1064 nm.
[0047] Example 5
[0048] The connection temperature in step (5) is 1500° C. The other steps are the same as those in Example 1. The bending strength of the joint obtained in this example is 388 MPa, and the light transmittance of the joint at a wavelength of 1064 nm is 82.1%.
[0049] Comparative Example 1
[0050] In step (5), the joint cooling rate was set to 20°C / min. All other steps were the same as in Example 1. The joint obtained in this example had a bending strength of 390 MPa and a light transmittance of 11.5% at a wavelength of 1064 nm. The slow cooling rate caused the weld glass to crystallize. While this crystallization did not reduce the joint strength, it significantly deteriorated the joint's light transmittance.
[0051] The performance parameters of sapphire ceramic and the glass solder obtained in Example 1 are shown in Table 1.
[0052] The joint strength and linear transmittance of the above embodiments and comparative examples are shown in Table 2.
[0053] Table 1 Performance parameters of sapphire ceramics and glass solder obtained in Example 1
[0054]
[0055] Table 2 Bending strength and light transmittance of joints of Examples and Comparative Examples
[0056]
Claims
1. A method for connecting transparent sapphire ceramics based on glass solder, characterized in that: The method uses glass solder to connect the sapphire ceramic mother material, and the raw materials of the glass solder are composed of the following in weight percentage: RE2O3: 30% to 40%, Al2O3: 5% to 10%, SiO2: 30% to 40%, B2O3: 10% to 20%, BaO: 5% to 10%, K2O: 5% to 10%.
2. The method for connecting transparent sapphire ceramics based on glass solder according to claim 1, characterized in that: The RE2O3 is one or more of white La2O3 and Y2O3.
3. The method for connecting transparent sapphire ceramics based on glass solder according to claim 1, characterized in that: In the glass solder composition, B2O3 is introduced from H3BO3, K2O is introduced from K2CO3, and BaO is introduced from BaCO3. The purity of each raw material is higher than 99.9%.
4. The method for connecting transparent sapphire ceramics based on glass solder according to claim 1, characterized in that: The connection method specifically includes the following steps: (1) Material preparation: After grinding and polishing the surface of the sapphire ceramic to be welded, ultrasonic cleaning is performed with acetone as the medium for 5-20 minutes, and then blown dry for later use; (2) Preparation of glass solder: weighing various oxide raw materials according to the composition of glass solder, uniformly mixing them, and preparing glass solder powder by melt-water quenching method; (3) Solder pre-sintering: Add polyvinyl alcohol to the glass solder powder and stir evenly, then put it into a tablet pressing mold to press it into a sheet structure with a certain thickness, and then put it into a muffle furnace for pre-sintering to obtain a glass solder sheet; (4) Joint assembly: The pre-sintered glass solder sheet is cut into a shape with the same size as the surface of the ceramic to be welded, and then placed between two polished sapphire ceramics to form a "sandwich" assembly structure. No pressure is used during the connection process; (5) Joint connection: The joint assembled in step (4) is placed in a muffle furnace in an air atmosphere and quickly heated to the welding temperature, and kept warm for a sufficiently long time. After the end of the heat preservation, it is quickly cooled to room temperature; (6) Joint annealing: The welded joint is placed in an air atmosphere muffle furnace again, heated to a certain temperature and kept at that temperature for a certain period of time, and then cooled to room temperature with the furnace.
5. The method for connecting transparent sapphire ceramics based on glass solder according to claim 4, characterized in that: In the step (1), the grinding and polishing method is: grinding with 600#, 1000#, and 1200# sandpaper in sequence, and then polishing with diamond polishing liquid with particle sizes of 2.5μm, 1.5μm, and 0.5μm in sequence.
6. The method for connecting transparent sapphire ceramics based on glass solder according to claim 4, characterized in that: In the step (2), the process of preparing glass solder powder by the melt-water quenching method is as follows: weighing the oxide raw material powder into a polytetrafluoroethylene ball mill, using alcohol as the ball milling medium and ZrO2 as the grinding balls for ball milling, the ball milling speed is 400-500 rpm, and the ball milling time is 2-5h; drying is performed after the ball milling is completed, and the dried material is poured into a platinum crucible, and placed in a muffle furnace with an air atmosphere and heated to 1500-1600°C. After keeping the temperature for 1-3h, the obtained glass melt is poured into deionized water to obtain glass fragments; the glass fragments are placed in an agate ball mill, and ball milled with agate as the grinding balls, the ball milling speed is 400-500 rpm, and the ball milling time is 2-5h. After the ball milling is completed, drying is performed, and the glass solder powder is obtained by sieving through a 200-mesh sieve.
7. The method for connecting transparent sapphire ceramics based on glass solder according to claim 4, characterized in that: In the step (3), the weight of the added polyvinyl alcohol is 1-5% of the weight of the glass solder powder; the pressed thickness of the flake glass solder is 0.1-0.3 mm, the pressure during pressing is 20-40 MPa, and the holding time is 1-5 min.
8. The method for connecting transparent sapphire ceramics based on glass solder according to claim 4, characterized in that: In the step (5), the heating rate of the joint connection process is 5-20°C / min, the connection temperature is 1400-1550°C, the insulation time is 10-30min, the cooling rate between the welding temperature and 750°C is higher than 40°C / min, and there is no requirement for the cooling rate below 750°C.
9. The method for connecting transparent sapphire ceramics based on glass solder according to claim 4, characterized in that: In step (5), cooling can be performed in the following manner: inert gas can be introduced into the furnace to accelerate the cooling of the joint to ensure that the cooling rate of the joint is higher than 40°C / min; the joint can also be taken out of the furnace and allowed to cool naturally in the air.
10. The method for connecting transparent sapphire ceramics based on glass solder according to claim 4, characterized in that: In the step (6), the joint annealing temperature is 800-860° C., and the annealing time is 2-5 hours.